PERTUMBUHAN DAN LAJU EKSPLOITASI IKAN TAMBAN (Sardinella albella Valenciennes, 1847) DI PERAIRAN SELAT MALAKA TANJUNG BERINGIN SERDANG BEDAGAI SUMATERA UTARA - Laily Dirda Fitrianingsih; Miswar Budi Mulya; Ani Suryanti (Program Studi Manajemen Sumberdaya Perairan, Fakultas Pertanian Universitas Sumatera Utara, 2015)
The high demand society of tamban (Sardinella albella) was effect fishermen makesfishing effort too much without control. This study has the objective on accesing the growthand exploitation rates of tamban in Malacca Strait Tanjung Beringin Serdang Bedagai. Thisstudy was held in three months, which are from March until May 2015. The data analysis usethe ELEFAN I method (Electronic Lenght Frequencys Assesment Tool) which packed inFISAT II (FAO-ICLARM Fish Stock Assesment Tool).The samples of tamban are 721 whichconsist of 465 male tamban and 256 female tamban. The growth pattern of tamban is negativeallometric. The range of condition factor are 0,630 – 1,633. The range of length frequencydistribution are 147 - 152 mm, the size group is dominating are 167 - 171 mm for maletamban and 157 - 167 mm for female tamban. The estimation of Von Bertalanffy growthparameter of male tamban are L∞ = 211,89 mm with K = 0,230 per year and t0 = -2,615 years,and female tamban are L∞ = 211,05 mm with K = 0,550 per year and t0 = -0,604 years. Totalmortality (Z) is 1,31 per year,the estimation natural mortality (M) is 0,49 per year. It showsthe estimation of exploitation rates are 0,65 per year.Keywords: growth, exploitation rates, Sardinella albella, Malacca Strait.